(untitled) (REGE Revista de Gestão, 2013)
The Local Production Arrangements (LPAs) have been considered important mechanisms of efforts aggregation, especially in the context of micro and small companies (MSCs), which are seeking to take advantage of this tool for insertion in the productive chains of large companies in various activity sectors. In this context, this study aimed to identify and analyze the main insertion advantages and difficulties encountered by participating and non-participating MSCs in the oil, gas and energy LPA in the municipality of Duque de Caxias. The research, whose methodology assumed a descriptive and exploratory nature, drew upon literature review and a data survey that interviewed 58 small executives in a universe of 800 MSCs. The findings point to a dissonance between the policy employed by LPA and the reality of the current scenario of local MSCs, evidenced by the demands they are submitted, which increase the integration difficulties in the productive chain of Oil, Gas and Energy. It was also possible to verify the need of a greater coordination between developer agencies and those responsible for policy guidelines in order to improve the conditions for a greater number of companies to qualify to be able to join the LPA.